Mitochondrial DNA-related Disorders. Issue 1 (13th June 2007) - Mancuso, Michelangelo; Filosto, Massimiliano; Choub, Anna; Tentorio, Marta; Broglio, Laura; Padovani, Alessandro; Siciliano, Gabriele
Abstract : Mitochondrial diseases are a group of disorders due to a mitochondrial respiratory chain deficiency. They may depend on mitochondrial genome ( mtDNA -related disorders) as well as on a nuclear genome defect ( nDNA -related disorders). mtDNA -related disorders encompass an increasing number of clinical pictures associated with more than 250 different provisional or confirmed pathogenic changes in mtDNA . Although some clinical syndromes are nosologically defined, most of the cases present with polymorphous phenotypes ranging from pure myopathy to multi-system involvement. Complexity of mitochondrial genetics is in part responsible for the extreme clinical intra- and inter-familial heterogeneity of this group of diseases. In this review, we briefly report an updated classification and overview the main clinical pictures of this class of diseases.